2012
DOI: 10.1074/jbc.m112.351783
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of ATF4 Gene by CCAAT/Enhancer-binding Protein β (C/EBPβ) Differentially Regulates Integrated Stress Response

Abstract: Background: eIF2ϳP induces translational expression of ATF4, an ISR transcription factor that regulates cell survival during stress. Results: The LIP isoform of C/EBP␤ represses ATF4 transcription during UV stress, reducing ATF4 mRNA available for preferential translation by eIF2ϳP. Conclusion: Transcription of ATF4 is controlled by different stress signaling pathways. Significance: Differential ISR expression during eIF2ϳP is important for alleviation of cell damage during environmental stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
1
36
1
Order By: Relevance
“…After translation of the uORF, a number of 40S ribosomes are suggested to scan past the initiation codon of the LAP isoform before reacquiring a new eIF2⅐GTP⅐Met-tRNA i Met complex and begin translation at the initiation codon of LIP. LIP expression is also elevated after UV irradiation, suggesting that decreased eIF2 ternary complex levels during cellular stress exacerbate this phenomenon (54). The related gene C/EBP␣ and its encoded protein isoforms are also translationally regulated by a 5Ј-proximal uORF (28,37,55).…”
Section: Translation Reinitiation and Differential Cds Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…After translation of the uORF, a number of 40S ribosomes are suggested to scan past the initiation codon of the LAP isoform before reacquiring a new eIF2⅐GTP⅐Met-tRNA i Met complex and begin translation at the initiation codon of LIP. LIP expression is also elevated after UV irradiation, suggesting that decreased eIF2 ternary complex levels during cellular stress exacerbate this phenomenon (54). The related gene C/EBP␣ and its encoded protein isoforms are also translationally regulated by a 5Ј-proximal uORF (28,37,55).…”
Section: Translation Reinitiation and Differential Cds Translationmentioning
confidence: 99%
“…For example, ATF4 expression is potently induced during endoplasmic reticulum stress, but there are only low levels of ATF4 expression during UV irradiation (54,81). Both conditions induce robust eIF2␣-P, and preferential translation of ATF4 mRNA occurs with either stress (81).…”
Section: Other Complexities Of Gene Expression Regulated By Uorfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this mechanism, we sought to determine whether TGR5-dependent activation of the mTOR pathway could be responsible for the increase in LIP in our model. Stimufactors (52)(53)(54)(55). We first investigated whether TGR5 could regulate C/EBPβ expression.…”
Section: Tgr5mentioning
confidence: 99%
“…We therefore concluded that the 33 kDa band represented LAP and the 37 kDa band LAP*, as previous studies indicated that p33 is mainly translated in mouse embryonic fibroblasts (MEF), NIH3T3, and 3T3-L1 cells. (30)(31)(32)(33) No band corresponding to LIP was detected (data not shown). Mouse C/EBPb is known to be localized in the nucleus, which was confirmed by immunostaining using 7H5 and 7D2 monoclonal antibody clones (Fig.…”
Section: Resultsmentioning
confidence: 89%